Shear strength parameters of sand-tire chips mixtures - Aksoy, Hüseyin Suha; Taher, Nichirvan Ramadhan; Awlla, Halmat Ahmed (Gumushane University, 2021)
Used tires are unwanted wastes especially in urban areas and their extent is growing every year. With the development of human societies and the increasing use of automobiles, every year millions of used tires are collected as garbage around the world and leave the consumption cycle. However, they can be used by mixing with soil, one of the basic building materials, to improve their mechanical properties. This article discusses the effect of adding tire chips on the shear strength properties of high-friction sand. Different mixing ratios of the sand-tire chips mixture by weight (100: 0, 97.5: 2.5, 95: 5, 92.5: 7.5 and 90:10) were used. The Maximum Dry Density (MDD) and Optimum Moisture Content (OMC) of sand and different sand-tire chip mixtures were determined by the standard Proctor test. Samples were prepared under OMC and MDD conditions and direct shear box test was performed on sand and sand-tire chip mixtures under three different axial stresses. The results showed that when the percentage of tire chips reaches 5%, the internal friction angle was increased by 13.8% and cohesion was decreased by 66.4%. After this point internal friction angle was decreased and cohesion increased slightly. © 2021, Gumushane University. All rights reserved.
Kum-öğütülmüş araç lastiği karışımlarının kayma mukavemeti parametreleri
Keywords: High friction sand; Proctor compaction test; Shear box test; Shear strength parameters; Tire chips